Uji Antelmintik dari Ekstrak Etanol Daun Kadamba (Mitragyna speciosa): Anthelmintic Test of Ethanol Extract of Kadamba Leave (Mitragyna speciosa) - Putri Natasya Magdalena; Juniza Firdha Suparningtyas; Islamudin Ahmad (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
Diseases caused by parasites, especially worms in animals on farms, are one of the problems that farmers often face. Worm disease can decrease the productivity of livestock and cause a decrease in the selling value of livestock at the market. The most common worm disease that attacks livestock is Paramphistomum sp. The treatment of this disease uses nutritious plants, which is one of the alternatives chosen to minimize side effects due to the administration of synthetic drugs. Kadamba leaf was chosen in this study because one of the medical plants that have potential compounds as anthelmintics. The aim of this research is to know the anthelmintic activity of kadamba leaf extract to Paramphistomum sp. 210 samples of Paramphistomum sp. were taken from cow rumen at Tanah Merah slaughterhouses. This study was conducted in vitro with seven experimental groups consisting of one positive control (Albendazole), one negative control (NaCl), and five groups of kadamba leaf extract with concentrations of 2,5%, 5%, 7,5%, 10 %, 12,5% with three replications. The results of the study showed the yield of kadamba leaf extract was 13,88%, and the anthelmintic test showed that kadamba leaf extract had anthelmintic activity against Paramphistomum sp. at all concentrations.